The influence of the Beijing Olympic Games on optimization of the sports industry structure in China - Chen, Y. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
The purpose of this paper is to systematically analyze the influence of the 2008 Beijing Olympic Games on optimizing the sports industry structure in China on the basis of sports industry and industrial economic theories. Methods: Diagnosis and comparative analysis were used to analyse the sports industry structure in China. China`s sports industry has developed quickly but the proportion of its increased value in GDP, GDSP is lower compared to some developed countries, and the gap between different regions is large. Moreover, the internal structure is not reasonable. Proportionally, the sports service industry has not increased in value as much as the sports industry as a whole; whereas the sports product industry`s value has increased more. The value of an increased sports industry is predominantly attributed to the sports service industry in developed countries. Results: The Beijing Olympic Games will provide a new impetus to the development of China`s sports industry, and will promote the development of the sports fitness and recreation industry, sports competition performance industry, and the sports agency industry. It will also promote the development of sports turism, sports media and other sports service industries. This will help to adjust and optimize the sports industry structure in China. On the other hand, the Beijing Olympic Games will promote regular operation in the sports market, expand the openness of the market, and will develop China`s sports industry. Discussion / Conclusions: As the existence of a post-Olympics effect is a barrier, action should be taken to reduce its influence whilst nurturing the opportunity to develop and optimize China`s sports industry.